Effect of Emotional Quotient Promoting Program on Emotional Quotient Among Nursing Students - นุชสุธรรม, วิลัยพร; แก้วกันทะ, พัชราวรรรณ; สมบูรณ์, ลาวัลย์; บุญไทย, ชมภู่; เมืองมาคำ, สุกัญญา (Nursing Journal CMU, 2018)
Emotional quotient is an emotional ability to live creatively and happily. Promoting emotional quotient among nursing students is very essential. This research was a quasi-experimental research using control and experimental groups. The purposes of this study was to examine the effect of emotional quotient promoting program among nursing students. The samples were first-year nursing students. There were 52 cases: 26 in the experimental group and 26 in the control group, using simple random sampling. The study was conducted between March to May, 2017. The experimental group received the emotional quotient promoting program. The control group did not participate in program. The research instruments included the emotional quotient promoting program, the personal data questionnaire, and the emotional quotient questionnaire. Data were analyzed using descriptive statistic, Mann-Whitney U test, and Wilcoxon signed rank test. The research found that the mean score of emotional quotient of the experimental group receiving the emotional quotient promoting program was statistically higher than that of the control group who did not receive the program at p < .05. In addition, the mean score of emotional quotient of the experimental group after receiving the emotional quotient promoting program was statistically higher than that of before at p < .001. The results of this research indicate that the emotional quotient promotion program could improve the emotional quotient of nursing students. Emotional quotient promotion should be continually with regular education.